Ethylene-1-13C (13C12CH4): First analysis of the ν2, ν3 and 2ν10 bands and re–analysis of the ν12 band and of the ground vibrational state. (January 2017) - Ulenikov, O.N.; Gromova, O.V.; Bekhtereva, E.S.; Aslapovskaya, Yu.S.; Tan, T.L.; Sydow, C.; Maul, C.; Bauerecker, S.
Abstract: High-resolution FTIR ro-vibrational spectra of the 13 C 12 CH4 molecule in the region of 600–1700 cm −1, where the bands ν 3, ν 12 and ν 2 are located, were recorded and analyzed with the Hamiltonian model. This model takes resonance interactions between these three bands as well as strong interactions with six neighboring bands, ν 10, ν 8, ν 7, ν 4, ν 6, and 2 ν 10 into account. More than 3800 ro-vibrational transitions belonging to the bands ν 3, ν 12, ν 2 and 2 ν 10 were assigned (for the first time for the ν 2, ν 3 and 2 ν 10 bands) with the maximum values of quantum numbers J max . / K a max . equal to 22/8, 52/18, 30/11 and 27/12, respectively. On this basis, a set of 62 vibrational, rotational, centrifugal distortion and resonance interaction parameters was obtained from the weighted fit. These parameters reproduce 1562 initial "experimental" ro-vibrational energy levels obtained from unblended lines with the rms error d rms = 2.6 × 10 − 4 cm − 1 . Furthermore, ground state parameters of the 13 C 12 CH4 molecule were improved. Abstract : Highlights: Ro-vibrational spectra of 12 C 13 CH4 . Resonance interactions in the 12 C 13 CH4 molecule. Determination of spectroscopic parameters.